2002
DOI: 10.1128/jb.184.14.4003-4017.2002
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia thailandensis E125 Harbors a Temperate Bacteriophage Specific for Burkholderia mallei

Abstract: Burkholderia thailandensis is a nonpathogenic gram-negative bacillus that is closely related to Burkholderia mallei and Burkholderia pseudomallei. We found that B. thailandensis E125 spontaneously produced a bacteriophage, termed E125, which formed turbid plaques in top agar containing B. mallei ATCC 23344. We examined the host range of E125 and found that it formed plaques on B. mallei but not on any other bacterial species tested, including B. thailandensis and B. pseudomallei. Examination of the bacteriopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
1
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 65 publications
(55 reference statements)
2
91
1
2
Order By: Relevance
“…The closest match for the head genes was found in the Burkholderia siphovirus phiE125. This is a surprising finding since phiE125 was isolated from a ␤-proteobacterium (224). Over its tail genes, the most closely related phage is Shigella phage SfV.…”
Section: Opportunistic Pathogens and Free-living Bacteriamentioning
confidence: 99%
“…The closest match for the head genes was found in the Burkholderia siphovirus phiE125. This is a surprising finding since phiE125 was isolated from a ␤-proteobacterium (224). Over its tail genes, the most closely related phage is Shigella phage SfV.…”
Section: Opportunistic Pathogens and Free-living Bacteriamentioning
confidence: 99%
“…However, Burtnick et al (2002) recently demonstrated that the lipopolysaccharide O-antigens of B. mallei and B. pseudomallei display differences in O-acetylation at position 4V of l-talose. This finding probably explains the presence of species-specific LPS O-antigen epitopes and the existence of B. mallei-specific monoclonal antibodies (Anuntagool and Sirisinha, 2002) and bacteriophages (DeShazer, 2004;Woods et al, 2002). However, these observations have not been exploited for development of rapid, simple diagnostic assays.…”
Section: Discussionmentioning
confidence: 94%
“…It should be noted that this serological test also cross-reacts with B. pseudomallei (DeShazer & Waag, 2004). To date, the only B. mallei-specific detection assay reported in the literature incorporates the bacterial phage phiE125, which has been shown to be specific for B. mallei capable of biosynthesizing LPS (Woods et al, 2002).…”
Section: Discussionmentioning
confidence: 99%